Fumonisins and their analogues in contaminated corn and its processed foods – a review. Issue 11 (2nd November 2018) - Ponce-García, Nestor; Serna-Saldivar, Sergio O.; Garcia-Lara, Silverio
ABSTRACT: One of the food security problems faced worldwide is the occurrence of mycotoxins in grains and their foods. Fumonisins (FBs) are mycotoxins which are prevalent in corn ( Zea mays L.) and its based foods. Their intake and exposure have been epidemiologically and inconclusively associated with oesophageal cancer and neural tube defects in humans, and other harmful health effects in animals. The toxic effects of FBs can be acute or chronic and these metabolites bioaccumulate mainly in liver and kidney tissues. Among FBs, fumonisin B1 (FB1 ) is the most relevant moiety although the 'hidden' forms produced after food thermal processes are becoming relevant. Corn is the grain most susceptible to Fusarium and FBs contamination and the mould growth is affected both by abiotic and biotic factors during grain maturation and storage. Mould counts are mainly affected by the grain water activity, the environmental temperature during grain maturation and insect damage. The abiotic factors affected by climatic change patterns have increased their incidence in other regions of the world. Among FBs, the hidden forms are the most difficult to detect and quantify. Single or combined physical, chemical and biological methods are emerging to significantly reduce FBs in processed foods and therefore diminish their toxicological effects. Graphical Abstract: